Nutritional Characterization of Street Food in Urban Turkmenistan, Central Asia - Albuquerque, Gabriela; Sousa, Sofia; Lança de Morais, Inês; Gelormini, Marcello; Motta, Carla; Gonzales, Gerard Bryan; Ovezov, Azat; Damasceno, Albertino; Moreira, Pedro; Breda, João; Lunet, Nuno; Padrão, Patrícia (Frontiers in Public Health, 2022)
Objective Describing the availability and nutritional composition of the most commonly available street foods in Ashgabat, Turkmenistan. Methods One hundred sixty-one street food vending sites (six public markets) were assessed, through a collection of data on vending sites' characteristics and food availability, and samples of commonly available foods (21 homemade; 11 industrial), for chemical analysis. Results Fruit, beverages, and food other than fruit were available in 6.8, 29.2, and 91.9% of all vending sites, respectively. Regarding the latter, 52.7% of the vending sites sold only homemade products (main dishes, snacks, cakes, biscuits and pastries, bread, ice-cream chocolate and confectionery, savory pastries and sandwiches), 37.2% only industrial (ice-cream, chocolate and confectionery, cakes, biscuits and pastries, snacks, bread and savory pastries) and 10.1% both. Homemade foods presented significantly higher total fat [homemade 11.6 g (range 6.6–19.4 g); industrial 6.2 g (range 4.0–8.6 g), p = 0.001], monounsaturated, polyunsaturated and trans-fat, and sodium and potassium content per serving. Industrial wafers presented the highest mean saturated (11.8 g/serving) and trans-fat (2.32 g/serving) content. Homemade hamburgers presented the highest mean sodium content (1889 mg/serving). Conclusions Strategies to encourage the production and sales of healthier street foods, especially homemade, are needed to promote healthier urban food environments in urban Turkmenistan.